The relevance of serum macrophage migratory inhibitory factor and cognitive dysfunction in patients with cerebral small vascular disease - Zhao, Jianhua; Wang, Xiaoting; Li, Qiong; Lu, Chengbiao; Li, Shaomin (Frontiers in Aging Neuroscience, 2023)
Cerebral small vascular disease (CSVD) is a common type of cerebrovascular disease, and an important cause of vascular cognitive impairment (VCI) and stroke. The disease burden is expected to increase further as a result of population aging, an ongoing high prevalence of risk factors (eg, hypertension), and inadequate management. Due to the poor understanding of pathophysiology in CSVD, there is no effective preventive or therapeutic approach for CSVD. Macrophage migration inhibitory factor (MIF) is a multifunctional cytokine that is related to the occurrence and development of vascular dysfunction diseases. Therefore, MIF may contribute to the pathogenesis of CSVD and VCI. Here, reviewed MIF participation in chronic cerebral ischemia-hypoperfusion physiology, including new evidence for CSVD, and its potential role in protection against VCI.